Transition Of Authority Judicial Institutions Simultaneous National Elections 2024 - Salahudin Pakaya; Roy Moonti; Yusrianto Kadir; Taufik Firmanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The decision of the Constitutional Court No. 97/PUU-XI/2013 resulted in changes in the function and authority of the judicial institution that adjudicates Pilkada. The Constitutional Court's decision then gave birth to Article 157 of Law No. 10 of 2016 Amending Law No. 8 of 2015 (Pilkada Law) which contains provisions for the establishment of a special election judicial body that will hear disputes over the results of simultaneous national elections in 2024. However, the establishment of a special election judicial body mandated by the Pilkada Law still faces juridical obstacles if it is linked to Law 48 of 2009 concerning Judicial Power, and laws governing judicial bodies under the auspices of the Supreme Court, especially the general and state administrative courts. Another juridical problem is the Constitutional Court Decision Number 85/PUU-XX/2022 which states that the phrase "until a special judicial body is established" in Article 157 paragraph (3) of the Pilkada Law does not have binding legal force. So that the Constitutional Court's decision can be interpreted as a sign of defining the Constitutional Court as a permanent judicial institution to hear disputes over Pilkada results. This research uses normative research methods as a characteristic of legal research, using statute law approaches, expert opinions. The purpose of this research is to search and find the right norms and have legal arguments in determining the right judicial institution authorized to hear disputes over the results of the 2024 simultaneous regional elections.